The Settlement of Cases of Annual Budgetary Misuse in Salongo Village, South Bolaang Mongondow Regency - Fahmi Djibran (Universitas Negeri Gorontalo, 2022)
This study aims to find out and analyze how the process of resolving cases of misuse of village funds in Salongo Village, Bolaang Mongondow Selatan Regency. This type of research is empirical research with a descriptive approach. Data obtained directly through observations and interviews from the regional inspectorate office of South Bolaang Mongondow Regency, and directly related parties. The results showed that the process of settling cases of misuse of village funds by village officials in salongo village tended to use the peaceful way. Where the mechanism taken is the family law route with the final administrative provision, namely a refund. It is often used by the parties concerned,As for the inhibiting factor in law enforcement against the misuse of village funds in Salongo Village, the Prosecutor's Office is less professional when receiving reports onlydirecting to be returned to the village only, in soft language telling the community to solve this problem in a family way. In addition, there is a lack of transparency, the minimal role of the community and other village officials who should be responsible for settlement efforts.